Estimation of Vitamin D Level in Patients of Chronic Liver Disease and its Association with Child Turcotte Pugh’s Score (Academia Journal of Medicine, 2021)
Background: Chronic liver disease (CLD) has a fairly high occurrence in the Indian subcontinent due to variety of etiological factors including alcohol abuse, viral hepatitis, etc. As liver plays a crucial role in digestive as well as metabolic functions, its significant dysfunction is related to severe imbalance of vitamin D. Though for long the role of vitamin D in bone mineral metabolism is known yet recent literature has suggested its significant role in immune modulation, inflammatory response and in fibrosis. Since insufficient data on vitamin D levels in CLD patients exists in Indian population, hence we planned this study. Subjects and Methods: Hundred patients of CLD were included in our study following approval from institutional ethics committee, obtaining informed written consent and excluding bone disease, chronic renal disease, known cardiac disease & known malignancy. All patients underwent estimation of vitamin D levels and appropriate tests to diagnose CLD with further categorization into A, B, C as per Child-Turcot-Pugh (CP) Criteria. Appropriate statistical tests were then applied to find out the association between CLD and vitamin D levels. Results: Majority of the CLD patients were males and in 3rd-5th decade with most of them i.e. 89% in our study, had insufficiency or deficiency of vitamin D in their serum with majority having moderate to severe grades of CLD as per CP score. This association was statistically significant with p value of less than
Keywords: Vitamin D; Chronic Liver Disease; Child Turcotte Pugh’s Score